(untitled) (Journal of Universal Science Research, 2025)
This thesis explores the integration of artificial intelligence (AI) and natural compounds in the development of modern pharmaceutical agents. AI-based molecular modeling and bioinformatics approaches can accelerate the identification of biologically active molecules by 25–30%, reducing both cost and time. Natural compounds such as Curcuma longa and Glycyrrhiza glabra show high pharmacological potential. The study emphasizes that combining computational prediction with experimental validation creates an innovative and sustainable approach to developing safe and effective medicines.